THE STATE OF LITHUANIAN MODERN BOOK SCIENCE - LIEPAITĖ, INGA (Knygotyra, 2015)
The beginning of development of Lithuanian modern book science is identified with the recreation of independence of Lithuania in 1990. The main research centre of book science – Institute of Book Science and Documentation of Faculty of Communication of Vilnius University – has formed, the yearly international conferences of book science have steadied and continuous publication “Knygotyra” has received recognition from Lithuania and abroad within nearly twenty year. These factors prompted the value of the state of Lithuanian book science and revelation of the influences by invoking the opinions of Lithuanian and foreign experts in book science. There were given the results of value of book science collected by an open-ended questionnaire from 29 respondents in this article. There were prepared two questionnaires for the research – individually for Lithuanian and for foreign respondents. There was aimed for more objective value of book science by this integrated research. Appealing to opinions of experts, the state of Lithuanian modern book science is represented by the following features: 1) systematic and continuous development of sci Abstractence, 2) the formation of strong traditions of the research work and continuity of traditions from generation to generation, 3) the purposeful activity of the main research centre of book science, 4) international recognition and importance of continuous publication “Knygotyra”, 5) high scientific and organizational level of yearly international conferences of book science, 6) the maturity of fundamental monographical and collective studies, 7) inducement of advance of book science internationally and role of Lithuanian book science how leader in neighbour Baltic states, 8) postgraduate and doctoral studies of book science are working. The further tasks and trends of Lithuanian book science should be formed considering the lack of conceptual opinions and independent studies of theory and methodology of book science, the partial arrears because of restrictions to research book history of some periods and fields sustained in Soviet Union, the changeable role of book, the quickness of internationalization of book market and growing significance of collaboration with schools and scientists of book science of Baltic and other neighbour states.